2016
DOI: 10.3171/2015.8.spine15119
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the utility of a laboratory-based spinal fixation training program for neurosurgical residents

Abstract: OBJECTIVE Pedicle and lateral mass screw placement is technically demanding due to complex 3D spinal anatomy that is not easily visualized. Neurosurgical and orthopedic surgery residents must be properly trained in such procedures, which can be associated with significant complications and associated morbidity. Current training in pedicle and lateral mass screw placement involves didactic teaching and supervised placement in the operating room. The objective of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 14 publications
(19 reference statements)
1
16
0
Order By: Relevance
“…Compared with no simulation training, cadaveric simulation‐trained learners showed significant improvement in most of the tested skill domains. When comparing behaviour change after training in low‐fidelity simulation‐trained and cadaveric simulation‐trained learners, the results were mixed.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Compared with no simulation training, cadaveric simulation‐trained learners showed significant improvement in most of the tested skill domains. When comparing behaviour change after training in low‐fidelity simulation‐trained and cadaveric simulation‐trained learners, the results were mixed.…”
Section: Resultsmentioning
confidence: 93%
“…Fifty‐one studies were included in the review, of which 47 were full‐text original research articles and four were conference posters. The main characteristics of studies, including OCEBM and mean MERSQI scores are shown in Tables S2 – S5 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 Using 10 subjects including residents and medical students, Sundar et al demonstrated a reduction in suboptimal screw placement after a sawbones and cadaver training module. 2023 Similarly, Harrop et al noted no statistically significant differences in pre- and postdidactic scores and in the OSATS using a Sawbones model for a posterior laminectomy with 8 subjects. 24 However, recent studies of orthopedic simulation programs have been able to demonstrate significantly improved cervical lateral mass and thoracic screw placement.…”
Section: Discussionmentioning
confidence: 98%